2021
DOI: 10.3390/pr9040707
|View full text |Cite
|
Sign up to set email alerts
|

A Process for Carbon Dioxide Capture Using Schiff Bases Containing a Trimethoprim Unit

Abstract: Environmental problems associated with the growing levels of carbon dioxide in the atmosphere due to the burning of fossil fuels to satisfy the high demand for energy are a pressing concern. Therefore, the design of new materials for carbon dioxide storage has received increasing research attention. In this work, we report the synthesis of three new Schiff bases containing a trimethoprim unit and the investigation of their application as adsorbents for carbon dioxide capture. The reaction of trimethoprim and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…Yaseen et al investigated Schiff bases derived from trimethoprim and aromatic aldehydes as adsorbents for carbon dioxide capture. Their high CO 2 adsorption capacity was attributed to the appropriate pore size distribution and the polar nature of the heteroatoms (N and O), as well as the Lewis-base nature of the new materials [ 37 ]. It was shown that polymers containing aromatic and phosphate units were suitable for CO 2 capture.…”
Section: Resultsmentioning
confidence: 99%
“…Yaseen et al investigated Schiff bases derived from trimethoprim and aromatic aldehydes as adsorbents for carbon dioxide capture. Their high CO 2 adsorption capacity was attributed to the appropriate pore size distribution and the polar nature of the heteroatoms (N and O), as well as the Lewis-base nature of the new materials [ 37 ]. It was shown that polymers containing aromatic and phosphate units were suitable for CO 2 capture.…”
Section: Resultsmentioning
confidence: 99%
“…Schiff bases 1-3 were prepared as previously stated 21 by reaction of trimethoprim moiety with the aryl aldehyde derivatives to obtain the required compounds Figure 1. Standard techniques were used to demonstrate the chemical structure of synthesized materials.…”
Section: Synthesis Of the Schiff Bases 1à3mentioning
confidence: 99%
“…The ease of manipulating the shape size of pores in MOFs with minor or rare chemical tuning making it attractive in improving the efficiency of the material for various applications [17,18]. In the quest for new adsorbents for CO 2 capture [41][42][43][44][45][46][47][48], we turned our attention to Schiff's base with metal complexes, because they are useful as biologically active compounds [19][20][21][22][23]. In particular, amoxicillin, which is used as an antibiotic to treat various infections, contains different aromatic rings and is characterized by high nitrogen and oxygen contents.…”
Section: Introductionmentioning
confidence: 99%